2024
DOI: 10.1038/s41392-023-01668-1
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoparticle-mediated combining therapy for human diseases

Xiaotong Li,
Xiuju Peng,
Makhloufi Zoulikha
et al.

Abstract: Combining existing drug therapy is essential in developing new therapeutic agents in disease prevention and treatment. In preclinical investigations, combined effect of certain known drugs has been well established in treating extensive human diseases. Attributed to synergistic effects by targeting various disease pathways and advantages, such as reduced administration dose, decreased toxicity, and alleviated drug resistance, combinatorial treatment is now being pursued by delivering therapeutic agents to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 530 publications
(518 reference statements)
0
3
0
Order By: Relevance
“…It involves the regulation of multiple signaling pathways through various therapeutic agents, such as drugs, antibodies, and nucleic acids. 63,64 However, different types of drugs have different sites and timings of action, and spatiotemporal control of drug release has become a key research direction in this field. 65 Therefore, there is an urgent need to develop SIPs responsive to multiple stimuli in the current era of precision medicine.…”
Section: Architecture Of Sipmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves the regulation of multiple signaling pathways through various therapeutic agents, such as drugs, antibodies, and nucleic acids. 63,64 However, different types of drugs have different sites and timings of action, and spatiotemporal control of drug release has become a key research direction in this field. 65 Therefore, there is an urgent need to develop SIPs responsive to multiple stimuli in the current era of precision medicine.…”
Section: Architecture Of Sipmentioning
confidence: 99%
“…Furthermore, tissue microenvironments consist of a combination of various physicochemical states, and by combining multiple stimuli, it is possible to improve the selectivity for specific physiological microenvironments through multiple affirmations. , More importantly, combination therapy is required because single treatment is often insufficient to achieve satisfactory therapeutic effects in the management of many diseases. It involves the regulation of multiple signaling pathways through various therapeutic agents, such as drugs, antibodies, and nucleic acids. , However, different types of drugs have different sites and timings of action, and spatiotemporal control of drug release has become a key research direction in this field . Therefore, there is an urgent need to develop SIPs responsive to multiple stimuli in the current era of precision medicine.…”
Section: Architecture Of Sipmentioning
confidence: 99%
“…Over the past several decades, clinical practice and exploratory studies have demonstrated that a singular treatment modality is ineffective in combating refractory diseases, such as cancer, diabetes, arthritis, and multiple sclerosis, due to its complexity, heterogeneity, and drug resistance. In line with therapeutic advancements, combination therapies have emerged as a superior approach to overcome monotherapy limitations. , Combination therapy, achieved by concurrently administering multiple drugs or integrating diverse therapeutic modalities, can enhance therapeutic effectiveness, minimize side effects, combat drug resistance, and mitigate the chances of recurrence. ,, For example, the highly active antiretroviral therapy, which involves the combination of three or more anti-HIV drugs, has become the predominant therapeutic approach for acquired immune deficiency syndrome. , Moreover, the World Health Organization recommends artemisinin combination therapy as the primary treatment for malaria patients . Significantly, the growing acknowledgment of the distinct benefits of combination therapy over monotherapy in treating various diseases has fostered its gradual adoption in clinical settings.…”
Section: Introductionmentioning
confidence: 99%